2020
DOI: 10.5194/amt-13-5407-2020
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a mass closure PM<sub>2.5</sub> composition online monitoring system

Abstract: Abstract. Online instruments have been widely applied for the measurement of PM2.5 and its chemical components; however, these instruments have a major shortcoming in terms of the lack or limited number of species in field measurements. To this end, a new mass closure PM2.5 online integrated system was developed and applied in this work to develop more comprehensive information on chemical species in PM2.5. For the new system, one isokinetic sampling system for PM2.5 was coupled with an aerosol chemical specia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…32 Differently, V and Ni showed high levels in summer due to the impact of ship emissions on the sea, and the high levels of Ca observed in summer and fall were related to dust from urban construction activities. 31 Although meteorological conditions have an effect on the diffusion of pollutant concentrations, long-term concentration changes in metals are less affected because of the low correlation between metal concentrations and typical meteorological conditions such as wind speed, temperature, wind direction, etc. (Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Differently, V and Ni showed high levels in summer due to the impact of ship emissions on the sea, and the high levels of Ca observed in summer and fall were related to dust from urban construction activities. 31 Although meteorological conditions have an effect on the diffusion of pollutant concentrations, long-term concentration changes in metals are less affected because of the low correlation between metal concentrations and typical meteorological conditions such as wind speed, temperature, wind direction, etc. (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work revealed that vehicle emissions were a major source of PM 2.5 in Shenzhen, accounting for ∼20% of the PM 2.5 mass concentrations. 31,32 Therefore, Shenzhen is a unique megacity offering an ideal environment for studying the sources and challenges of PM 2.5 health risks, especially those from vehicles including new energy cars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor 4 can be identified as a source of dust source (DS). This factor was distinguished by higher loadings of crustal elements such as Ca, Fe, and Ba (Lyu et al 2016;Su et al 2020). In factor 5, Cr, Mn, Fe, and Ni accounted for a relatively higher proportion (Taiwo et al 2014).…”
Section: Source Apportionmentmentioning
confidence: 99%
“…The potential source contribution function (PSCF) (Ashbaugh et al 1985;Su et al 2020) was commonly used to access the potential sources of pollutants, but this method can only reflect the proportion of pollution trajectories in each grid and cannot distinguish the differences between moderate and severe sources when PM 2.5 concentrations are slightly or much higher than the standard. In order to emphasize the spatial variation of the concentration of pollution source, the concentration-weighted trajectory (CWT) was used to calculate the potential source concentration weight of airflow trajectory in area, to show the variation of sources of PM 2.5 before and after the outbreak of the epidemic more visually.…”
Section: Concentration-weighted Trajectory (Cwt)mentioning
confidence: 99%